AB0741 Psoriatic arthritis quality of life questionnaire: translation, cultural adaptation and validation into portuguese language. (15th June 2017) - Barcelos, A; Ambrόsio, C; Silva, J da; McKenna, S; Wilburn, J; Ferreira, PL
Abstract : Background: Psoriatic Arthritis (PsA) has a strong negative impact in the quality of life of patients, through pain, stiffness, functional disability, deformity and a variety of other dimensions. The Psoriatic Arthritis Quality of Life (PsAQoL) questionnaire is a disease-specific instrument developed to measure quality of life in patients with PsA. Objectives: The aims of this study were to culturally adapt the questionnaire for Portugal, and evaluate its reliability and validity in patients with PsA. Methods: The original UK English version of PsAQoL was translated into Portuguese by a bilingual translation panel. An independent lay panel reviewed the instrument's item phrasing to ensure appropriateness in colloquial European Portuguese. Structured cognitive debriefing interviews were conducted with ten PsA patients to assess the acceptability, the understanding and the redundancy or ambiguity of the questionnaire. The Portuguese PsAQoL was subsequently applied to PsA patients followed at the Rheumatology Department of Centro Hospitalar do Baixo Vouga, E.P.E. To assess reproducibility, thirty patients with PsA completed the Portuguese PsAQoL on two occasions, two weeks apart. A larger sample was recruited to determine internal consistency and construct validity. Descriptive statistical analysis was used to characterize the data. The Nottingham Health Profile (NHP) was used as a comparator instrument. Results: Translation and adaptation were successful. The validation sample included 104 patients, 67% of whom were men. Their median age was 50.2 (SD=12.1) years and most were married. Cronbach's alpha for the Portuguese version of the PsAQoL was 0.91 and the test-retest reliability was 0.92, indicating that the measure has good internal consistency and produces low random measurement error. The PsAQoL could distinguish between groups of patients defined by self-reported general health status, self-reported severity of PsA and flare of arthritis. Duration of arthritis did not influence PsAQoL scores. There was a positive correlation between the total score of APsQoL and each of the dimensions of the NHP. Conclusions: The Portuguese version on the PsAQoL was found to be relevant, understandable and easy to complete, reliable and valid. It should be considered for use in clinical practice and research settings to asses PsA-specific QoL. References: McKenna S, Doward LC, Whalley D, et al. Development of the PsAQoL: a quality of life instrument specific to psoriatic arthritis. Ann Rheum Dis 2014; 63(2): 162–169. Wink F, Arends S, McKenna S, et al. Validity and reliability of the Dutch adaptation of the Psoriatic Arthritis Quality of Life (PsAQoL) Questionnaire. PloS One 2013; 8(2): e55912. Billing E, McKenna S, Staun M & Lindqvist U. Adaptation of the Psoriatic Arthritis Quality of Life (PsAQoL) instrument for Sweden. Scand J Rheumatol 2010; 39: 223–228. Disclosure of Interest: None declared